Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.7 Radical Expressions - R.7 Exercises: 88

Answer

$\color{blue}{34}$

Work Step by Step

RECALL: $a^3+b^3=(a+b)(a^2-ab+b^2)$ Use the formula above with $a=\sqrt[3]{7}$ and $b=3$ to obtain: $(\sqrt[3]{7}+3)(\sqrt{7^2}-3\sqrt[3]{7}+9) \\=(\sqrt[3]{7})^3+3^3 \\=7+27 \\=\color{blue}{34}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.